2010
DOI: 10.1111/j.1464-5491.2010.03099.x
|View full text |Cite
|
Sign up to set email alerts
|

Cord blood telomere length, telomerase activity and inflammatory markers in pregnancies in women with diabetes or gestational diabetes

Abstract: We found no difference in cord blood telomere length in pregnancies of women with diabetes compared with control subjects, but higher cord blood telomerase activity in Type 1 and gestational diabetes. This may reflect upregulated telomere reverse transcriptase in response to in utero oxidative DNA and telomere damage. These observations are relevant to the hypothesis that diabetes during pregnancy leads to in utero preprogramming towards senescence in the offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 23 publications
(30 reference statements)
4
31
1
Order By: Relevance
“…Still, whether these or other factors might be the determining ones of the modifications of the telomere length in LGA babies remains to be explored. In agreement with the hypothesis of the in utero reprogramming toward senescence, previous evidence showed higher cord blood telomerase activity in Type 1 and gestational diabetes34.…”
Section: Discussionsupporting
confidence: 90%
“…Still, whether these or other factors might be the determining ones of the modifications of the telomere length in LGA babies remains to be explored. In agreement with the hypothesis of the in utero reprogramming toward senescence, previous evidence showed higher cord blood telomerase activity in Type 1 and gestational diabetes34.…”
Section: Discussionsupporting
confidence: 90%
“…This result indicated that Sitagliptin might protect pancreatic β-cells from damage by elongating the length of its telomere (Ma et al, 2014). Moreover, a previous study performed on cord blood samples from pregnant women with pregestational T1DM, T2DM and gestational diabetes found significant differences between groups telomerase activity (it was high in cord blood from Type 1 and gestational diabetes pregnancies, but not in Type 2 diabetes) (Cross et al, 2010).…”
Section: Discussionmentioning
confidence: 94%
“…Little is known about DNA damage in pregnancy, especially in pregnancy complicated by pregestational (T1DM or T2DM) or gestational diabetes mellitus (GDM) [7, 3739, 41, 49]. …”
Section: Hyperglycemia Dna Damage and Pregnancy: Results Of Expementioning
confidence: 99%
“…No difference was found in cord blood telomere length in pregnancies of women with diabetes compared with control subjects, but higher telomerase activity was observed in Type 1 and GDM groups. The upregulation of telomerase may be a compensatory response to in utero oxidatively generated DNA and telomere damage [41]. …”
Section: Hyperglycemia Dna Damage and Pregnancy: Results Of Expementioning
confidence: 99%